A novel starch-based microparticle with polyelectrolyte complexes and its slow digestion mechanism. (February 2023) - Li, Suhong; Zhao, Qiyue; Wang, Siyu; Bai, Yan; Guo, Kai; Liu, Peng; Hu, Xiaopei; Li, Tuoping
Abstract: Encapsulation with polyelectrolyte complexes (PECs) was a novel approach to construct the starch based-microparticle with slow digestibility. In this study, sodium alginate (SA), gellan gum (GG) and chitosan (CS) were used to prepare SA/GG/CS based-PECs, while potato starch (PS) or its complex with lauric acid (PSL) were taken as the starch materials to obtain the starch based-microparticles (PSM or PSLM, respectively). The characteristic properties, morphological features, stability, and in vitro digestibility of their microparticles were investigated. From structure aspect, the PECs were steadied by the electrostatic interactions from negative and positive donors, and wrapped around starch granules to form the highly-hydroscopic hydrogel. This structure could withstand the heating treatment and in vitro simulated digestive fluid to some extent, thereby exhibiting better stability and slower digestibility than starch samples. Also, the slowly digestible starch content and the resistant starch content could be preserved at high levels, especially for PSLM. Besides, the release rate of lauric acid from PSLM was still low during the in vitro simulated digestion, which was also beneficial to health in terms of fatty acid intake. Hence, that was to say that the starch microparticle with SA/GG/CS based-PECs had the potential to be utilized in diet for hyperglycemia patients. Graphical abstract: Image 1 Highlights: Encapsulation with polyelectrolyte complexes reduced the starch digestibility. The complication of SA and GG was used as the negative-charge donor in PECs. The starch based-microparticles encapsulated with PECs had better heating stability. Encapsulation with PECs could retain the RS content.